ANALISIS POTENSI SEKTOR PARIWISATA SEBAGAI SEKTOR UNGGULAN DI WILAYAH JAWA TIMUR - Muktiyah Kumala; Aris Soelistiyo; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2017)
East Java province has great tourism potential with a development based on tourism that can provide economic growth to East Java province. The purpose of research to determine which districts / municipalities that the tourism sector as the leading sector in East Java Province and to know the pattern of growth and economic structure in each region in eastern Java. Data analysis method used is LQ analysis tools and Typology klassen. The result of the research shows that based on LQ analysis, there are some areas that show the potential of base and non base seen from the added value of tourism sector obtained from PDRB sub sector that support tourism sector potential. For the results of research using klassen typology is divided into 4 classifications that is one region included in the category of fast-growing and fast growing regions, two regions are included in the category of advanced but depressed regions, 35 regions that enter in fast developing areas and two regions included in the classification area relatively left behind.Keywords: PDRB 38 regency / city,  LQ and typology Klassen.